Microemulsion-based hydrogel formulation for transdermal delivery of dexamethasone - Chandra, Amrish; Sharma, Pramod Kumar; Irchhiaya, Raghuveer (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this study was to construct a microemulsion-based hydrogel formulation for the transdermal deliveryof dexamethasone. Almond oil, olive oil, linseed oil, and nutmeg oil were screened as the oil phase. A microemulsionbased system was chosen due to its good solubilizing capacity and skin permeation capabilities. The pseudoternary phase diagrams for microemulsion regions were constructed using various oils, egg lecithin as the surfactant, isopropyl alcohol (IPA) as the cosurfactant, and distilled water as the aqueous phase. Microemulsion gel formulations were prepared using Carbopol and filled into a reservoir-type transdermal system. The ability of various microemulsion formulations to deliver dexamethasone through the rat skin was evaluated in vitro using Keshary Chien diffusion cells. In order to enhance permeation, the skin was treated with an abrading gel (apricot seed powder in hydrogel base). The in vitro permeation data showed that microemulsions increased the permeation rate of dexamethasone compared with the control. The optimum formulation consisting of 0.1% dexamethasone, 10% olive oil, 70% egg lecithin:IPA (2:1), and water showed a permeation rate of 54.9 Î¼ g/cm2/h. The studied microemulsion-based hydrogel was stable toward centrifugation test and was nonirritating to the skin. The pharmacodynamic studies indicated that microemulsion based on nutmeg oil demonstrated a significantly (P < 0.05) higher anti-inflammatory potential. The nutmeg oil-based transdermal microemulsion gel system demonstrated 73.6% inhibition in rat paw edema. Thus, microemulsion-based transdermal systems are a promising formulation for dermal delivery of dexamethasone.